Hukum Mempelajari Ilmu Hal Pasal 1 - Wahyu Pratama; Dewi Kurniawati (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research examines the law of studying science in article 1, that science is always developing until now. This study aims to understand the general view of the obligation to study knowledge, hadith about the obligation to study knowledge, and how the ethics of studying knowledge. This study concludes that the law of studying knowledge explains that studying knowledge is one of the most important parts of human life, without knowledge humans will not be able to develop. Demanding knowledge is also considered as a starting point in fostering awareness in behavior. Moreover, in the concept of Islam there is a belief that emphasizes that learning is an obligation and sinful for those who leave it. This belief is so shaping in believers, so they have a high learning ethos and are full of enthusiasm and expect God's “sublime promise” as said in His verse.